METODE PEMBELAJARAN BAHASA ARAB - Ronaa Fitri Butsainah; Umi Hijriyah; Abdurochman (Makkah: Journal Of Islamic Studies, 2025)
This study examines the development of Arabic in the context of learning and its teaching methodology, as well as its position within the dynamics of Islamic history and linguistics. The study focuses on the definition of Arabic language learning, its objectives and principles, the elements of the Arabic language, and the various teaching methods that have developed and are used in the learning process. This study aims to provide a comprehensive understanding of the concept of Arabic language learning and relevant methods to improve the effectiveness of Arabic language mastery, both orally and in writing. The research method used is a descriptive-qualitative method through a literature study by reviewing books, scientific journals, and academic sources related to Arabic language learning. The results of the study indicate that the success of Arabic language learning is greatly influenced by the selection of appropriate methods, understanding of learning principles, and mastery of language elements. Thus, the integration of varied and contextual learning methods is the main key to improving students' Arabic language competence.